(untitled) (Colloquia Comparativa Litterarum, 2025)
This issue of the annual review Colloquia Comparativa Litterarum (the third since the inaugural one in 2015) has been composed in three parts: 1. Pars pro toto. The Literary Balkans in Europe 2. Miscellanea 3. Book Reviews